Comparison of patient intake of ticagrelor, prasugrel, or clopidogrel on restoring platelet function by donor platelets. Issue 6 (15th January 2015) - Scharbert, Gisela; Wetzel, Leonore; Schrottmaier, Waltraud C.; Kral, Julia B.; Weber, Thomas; Assinger, Alice
<x xml:space="preserve">Abstract</x> Background Bleeding complications are a common side effect in patients under dual antiplatelet (anti‐PLT) therapy. PLT transfusion provides a treatment option for these patients. However it is currently unclear if, and to what extent, P2Y12 inhibitors influence PLT function of donor PLTs and if patients taking these medications are likely to benefit from PLT transfusions. Study Design and Methods We investigated the effect of blood and plasma of clopidogrel‐, prasugrel‐, and ticagrelor‐treated patients on PLT function of blood from healthy volunteers in flow cytometry, light transmission aggregometry, and multiple electrode aggregometry (MEA). Results Our results demonstrate that clopidogrel had no and prasugrel had only mild effects on donor PLT function, but the reversible P2Y12 inhibitor ticagrelor completely abolished adenosine diphosphate‐mediated PLT activation in all assays tested. We further show that ticagrelor itself and not elevated adenosine concentrations in patient plasma were responsible for the observed effects. Moreover, we show that a modified MEA assay could provide a simple and rapid tool to allow determination of whether patients are likely to benefit from PLT transfusions. Conclusion Our results provide novel insights into potential differences between the P2Y12 inhibitors on donor PLT function in an in vitro setting, which may provide implications for future PLT transfusion strategies in these patients.